ANALISIS YURIDIS AKTA DI BAWAH TANGAN YANG DI WAARMEKING DAN DI LEGALISASI - Wahyu Triashari, N; Putri M.E. Purwani, Sagung (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
This paper shall be entitled as "Juridical Analysis of Onderhand Act which is Legalized and Waarmeking". It shall apply normative legal research and statutory approach. A difference existed among legalized onderhand act and the waarmeking one. It shall be observed upon the point of party and Notary signatories. Both onderhaand act and waarmerking ones which had been legalized shall be eligible before the court ass evidence in equal degree, however its legal power shall be different. Legalized shall be more affirmed compared to that waarmerking due to the presence of signature before the Notary.
Keywords: waarmeking, legalization, difference, evidence before the court